Evaluating the Food Properties of Canned Beef Rendang to Determine the Product Quality - Amdani, Rima Zuriah; Kusumaningrum, Annisa; Amri, Aldicky Faizal; Nurhikmat, Asep; Susanto, Agus; Siswoprayogi, Siswoprayogi; Praharasti, Anggita Sari (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Canning is a common method for preserving food, but its application to traditional cuisine is a new concept for Indonesian small and medium enterprises (SMEs), which typically focus on freshly served dish. Several studies have shown that the use of this method has the potential to extend the durability and marketability of beef rendang. Therefore, this study aimed to evaluate the food properties (sensory, proximate, color, spectroscopy, and physiochemical) of canned beef rendang to its suitability for consumption. Canning was carried out using the sterilization method at a temperature of 121 0 C and pressure of 0.7-0.9 bar. The sensory test of the canned product obtained was performed using a questionnaire, exploring various properties, including appearance, color, taste, aroma, and texture, while the proximate analysis was conducted by PT Saraswanti Indo Genetech laboratory. The color analysis was measured with a chromameter Konica Minolta CM-5 using the petri dish method, while the spectroscopy analysis was performed with an FTIR instrument from Brucker Vertex-80 using the ATR technique. Subsequently, moisture content was statistically analyzed using one-way and two-way ANOVA with a 95% confidence level. The sensory test results of canned beef rendang showed a 4.52 rating on a maximum scale of 5. The sterilization value (F0) was 3.819 minutes, which met the BPOM requirement of >3 minutes. The findings showed that the proximate analysis was consistent with the SNI standard, while the spectroscopy analysis indicated an unchanged functional group compared to the initial condition. The canned product was reported to have an increased trend of moisture content, but the range did not exceed the permissible limit of 60%. In addition, the pH and TBA value obtained were 5.745-5.315 and 0.1859-0.3195 mg/kg, respectively. The normal pH range of canned beef was typically 5.3-5.7, indicating that the value recorded met the established standard. Meanwhile, the TBA range obtained was significantly lower than the value of spoiled beef at 1.8 mg/kg. Based on these results, canned beef rendang was edible and safe for consumption.